The tale of the giant turnip : a book about generosity and greed ([Hong Kong] : Time Life Asia, 1997)
A poor farmer is amazed to find an enormous turnip growing in his field. He presents the unusual turnip to his king as a gift and is well rewarded for his generosity. When the poor farmers rich brother thinks up a plan to find the same good fortune for himself, he finds that greed only leads to misfortune.
Keywords: Values -- Juvenile literature; Generosity -- Juvenile literature